A karyological study of Suriana maritima L. (Surianaceae) from Xisha Islands of South China Sea. Issue 2 (3rd April 2018) - Liu, Junfang; Li, Shengchun; Chen, Haojie; Tu, Tieyao; Zhang, Dianxiang
Abstract: The present paper deals with the detailed cytological study of Suriana maritima L. (Surianaceae) from the Xisha Islands (also known as Paracel Islands) of South China Sea. The somatic chromosome number of the species is 18 and the karyotype formula is 2 n = 2 x = 18 m. The interphase nucleus is classified as round prochromosome. This is the first karyological investigation in Surianaceae, and the results provide new insights into the cytological characteristics of the plant family.